Teacher competence and preparedness for inclusive physical education (2020-2025): a systematic review of empirical evidence - Aidil Syaputra; Jeki Haryanto (Journal of Educational and Learning Studies, 2026)
@font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;}@font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-469750017 -1040178053 9 0 511 0;}@font-face {font-family:"Calisto MT"; panose-1:2 4 6 3 5 5 5 3 3 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-font-kerning:0pt; mso-ligatures:none; mso-fareast-language:EN-ID;}div.WordSection1 {page:WordSection1;} Teachers who are knowledgeable, self-confident, and well-trained to teach students with different abilities are a major requirement for inclusive physical education (IPE). However, the information on what determines this readiness is scattered across different disciplines and countries. This systematic review combined peer-reviewed research on the abilities and readiness of physical education (PE) teachers and pre-service teachers for inclusive teaching. The review was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines and utilized the Scopus database to retrieve records through a structured Boolean search targeting teacher competence, self-efficacy, preparedness, and inclusive or adapted physical education. Out of 487 records found, 31 empirical studies that were published within the period 2020-2025 met the eligibility criteria after removing duplicates, screening titles and abstracts, and assessing full texts. Records were retrieved from Scopus (search executed December 2025); eligibility followed predefined PICOS criteria, methodological adequacy was appraised with the FICO framework, and findings were combined through thematic synthesis. Screening was conducted with a documented reviewer-agreement procedure.  A thematic synthesis grouped the results based on four RQs that covered main competencies, obstacles, and enablers, the impact of teacher education and PD, and pedagogical-technological innovations. Two points were most prominent: self-efficacy through focused training is always changeable, and insufficient, fragmented preparation remains a structural barrier in different systems. The review deepens a situational understanding of inclusive-PE preparedness and gives practical recommendations for teacher-education programs and ongoing PD. Future studies are expected to use longitudinal methodologies, standardized competence instruments and also focus on under-represented regions to strengthen the evidence base.